Understanding how and why audits work: protocol for a realist review of audit programmes to improve hospital care. Issue 6 (14th June 2017) - Hut-Mossel, Lisanne; Welker, Gera; Ahaus, Kees; Gans, Rijk
Abstract : Introduction: Many types of audits are commonly used in hospital care to promote quality improvements. However, the evidence on the effectiveness of audits is mixed. The objectives of this proposed realist review are (1) to understand how and why audits might, or might not, work in terms of delivering the intended outcome of improved quality of hospital care and (2) to examine under what circumstances audits could potentially be effective. This protocol will provide the rationale for using a realist review approach and outline the method. Methods and analysis: This review will be conducted using an iterative four-stage approach. The first and second steps have already been executed. The first step was to develop an initial programme theory based on the literature that explains how audits are supposed to work. Second, a systematic literature search was conducted using relevant databases. Third, data will be extracted and coded for concepts relating to context, outcomes and their interrelatedness. Finally, the data will be synthesised in a five-step process: (1) organising the extracted data into evidence tables, (2) theming, (3) formulating chains of inference from the identified themes, (4) linking the chains of inference and formulating CMO configurations and (5) refining the initial programme theory. The reporting of the review will follow the 'Realist and Meta-Review Evidence Synthesis: Evolving Standards' (RAMESES) publication standards. Ethics and dissemination: This review does not require formal ethical approval. A better understanding of how and why these audits work, and how context impacts their effectiveness, will inform stakeholders in deciding how to tailor and implement audits within their local context. We will use a range of dissemination strategies to ensure that findings from this realist review are broadly disseminated to academic and non-academic audiences. PROSPERO registration number: CRD42016039882.